Customized birthweight standard for an Iranian population. (17th November 2021) - Nasri, K.; Hantoushzadeh, S.; Hugh, O.; Heidarzadeh, M.; Habibelahi, A.; Shariat, M.; Tara, F.; Kashanian, M.; Radmehr, M.; Yekaninejad, M. S.; Homeira, V. C.; Francis, A.; et al.
Abstract: Objective: To produce a customized birthweight standard for Iran. Method: Retrospective study of a pregnancy database collected from five hospitals across Iran. The cohort consisted of 4994 consecutive term births with complete data, delivered between July 2013 and November 2014. Coefficients were derived using a backwards stepwise multiple regression technique. Results: Maternal height, weight in early pregnancy and parity as well as the baby's sex were identified as significant physiological variables affecting birthweight. Paternal height and weight were also significant although weaker factors. The expected 280-day birthweight, free from pathological influences, of a standard size mother (height 163 cm, weight 64 kg) in her first pregnancy was 3390 g. Pathological factors found to affect birthweight in this cohort included village housing, anemia, preexisting and gestational diabetes and preeclampsia. Conclusion: The analysis confirmed the main physiological variables that affect birthweight in other countries and shows paternal factors also to be significant variables. Development of a country-specific customized birthweight standard will aid clinicians in Iran to distinguish between fetuses that are either constitutionally or pathologically small, thereby avoiding unnecessary interventions, and improving identification of at-risk pregnancies and perinatal outcome.